Detection of Knockdown-Resistance Homozygous Mutant C1534C using Allele-Specific Polymerase Chain Reaction in Aedes Albopictus and Aedes Aegypti - Fadila, Syananda Zahra; Setiawan, Ahmad Rudi; Fauziyah, Shifa; Madaniyah, Safira; Dewi, Eryantika Cipta; Naw, Sin War; Cahyaningrum, Sari Edi; , Tukiran; Sucipto, Teguh Hari (Folia Medica Indonesiana, 2023)
Highlights: • This research analyzed a previously understudied subject in Surabaya, Indonesia, and discovered knockdown resistance (kdr) mutations in Aedes albopictus. • The findings of this study can prompt further research, including bioassay testing and the development of more potent insecticides. Abstarct : Dengue hemorrhagic fever (DHF) has been endemic in Indonesia for decades. Insecticides are necessary to manage the transmission of the dengue virus. However, prolonged use of insecticides can lead to insecticide resistance. This study aimed to examine the genotype of mosquitoes using the allele-specific polymerase chain reaction (ASPCR) method. The ASPCR method was chosen for genotype detection due to its high sensitivity, affordability, and ease of design. Five mosquitoes were collected from human habitation in four different areas of Surabaya, Indonesia, namely Kranggan, Ulul Azmi Mosque, Ploso, and Kalijudan. Among them, three samples were identified as Aedes albopictus (A1, A2, and A5) and two samples were identified as Aedes aegypti (A3 and A4). The frequency of resistant alleles was analyzed using the Hardy-Weinberg package in RStudio version 2023.03.1. This study revealed that two mosquitoes carried homozygous mutant alleles with a band of 113 bp and three mosquitoes carried homozygous wild-type alleles with a band of 93 bp. Cysteine-to-cysteine (C/C) mutations and phenylalanine-to-phenylalanine (F/F) mutations at codon 1534 were observed in Aedes aegypti and Aedes albopictus mosquitoes. The homozygous mutant alleles were found in Kranggan, Surabaya, Indonesia. Further research is required to assess insecticide resistance and knockdown resistance (kdr)-like mutation by collecting more representative samples from larger areas within the region of Surabaya. Nevertheless, this study can be used as a reference for vector control and early prevention of dengue fever.